2016
DOI: 10.1111/1755-0998.12540
|View full text |Cite
|
Sign up to set email alerts
|

Sex determination in the wild: a field application of loop‐mediated isothermal amplification successfully determines sex across three raptor species

Abstract: 18PCR-based methods are the most common technique for sex determination of birds. 19Although these methods are fast, easy and accurate, they still require special facilities 20 that preclude their application outdoors. Consequently, there is a time lag between 21 sampling and obtaining results that impedes researchers to take decisions in situ and in 22 real time considering individuals' sex. We present an outdoor technique for sex 23 determination of birds based on the amplification of the duplicated sex-chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 36 publications
0
48
0
Order By: Relevance
“…These characteristics provide results in a fast, efficient, and cost-effective method that theoretically should amplify target sequences with higher specificity than PCR. Since its introduction, LAMP has seen wide interdisciplinary application, for example in detecting microorganisms (e.g., bacteria23, fungi4, and viruses56) diagnosing genetic diseases7, and even early sex determination8.…”
mentioning
confidence: 99%
“…These characteristics provide results in a fast, efficient, and cost-effective method that theoretically should amplify target sequences with higher specificity than PCR. Since its introduction, LAMP has seen wide interdisciplinary application, for example in detecting microorganisms (e.g., bacteria23, fungi4, and viruses56) diagnosing genetic diseases7, and even early sex determination8.…”
mentioning
confidence: 99%
“…[42] In a different context, Centeno-Cuadros et al developed a LAMP protocol for sex determination of raptor species. [43] In comparison with PCR-based methods, LAMP amplification demonstrates better sensitivity and specificity. Wang et al demonstrated that this method was more sensitive and reliable than conventional PCR or multiplex for the detection of Arcobacter species.…”
Section: Loop-mediated Isothermal Amplification (Lamp)mentioning
confidence: 99%
“…Moreover, product detection can be achieved directly within the reaction tube by a diagnostic color change and fluorescence, eliminating the need for electrophoretic techniques and related equipment (Centeno-Cuadros, Abbasi, & Nathan, 2017;Lee, 2017;Mori, Nagamine, Tomita, & Notomi, 2001). Moreover, product detection can be achieved directly within the reaction tube by a diagnostic color change and fluorescence, eliminating the need for electrophoretic techniques and related equipment (Centeno-Cuadros, Abbasi, & Nathan, 2017;Lee, 2017;Mori, Nagamine, Tomita, & Notomi, 2001).…”
mentioning
confidence: 99%
“…This method has also been used for sex determination in a number of organisms, including plants (Fujita et al, 2017;Hsu, Gwo, & Lin, 2012;Shiobara et al, 2011), fish (Hsu, Adiputra, Ohta, & Gwo, 2011), mammals (Khamlor et al, 2015;Nogami, Tsutsumi, Komuro, & Mukoyama, 2008), and birds (Centeno-Cuadros et al, 2017;Centeno-Cuadros, Tella, Delibes, Edelaar, & Carrete, 2018;Chan et al, 2012;Kim et al, 2015). This method has also been used for sex determination in a number of organisms, including plants (Fujita et al, 2017;Hsu, Gwo, & Lin, 2012;Shiobara et al, 2011), fish (Hsu, Adiputra, Ohta, & Gwo, 2011), mammals (Khamlor et al, 2015;Nogami, Tsutsumi, Komuro, & Mukoyama, 2008), and birds (Centeno-Cuadros et al, 2017;Centeno-Cuadros, Tella, Delibes, Edelaar, & Carrete, 2018;Chan et al, 2012;Kim et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation